Quality evaluation of innovative buttermilk biscuits produced from orange-flesh sweet potato flour infused with coconut - Ramsaran, Ronnie; de Gannes, Vidya; Eudoxie, Gaius (Frontiers in Food Science and Technology, 2024)
Introduction This study was undertaken to evaluate a value-added innovative buttermilk biscuit made from orange flesh sweet potato (OFSP) flour, infused with coconut. It underscores the importance of food utilisation through alternatives to wheat flour contributing to food and nutrition security amidst evolving global challenges. The objectives of this study were: to investigate the effect of different levels of OFSP flour with and without shredded coconut on the physical, microbiological, nutritional and sensory properties of buttermilk biscuits. The hypotheses were: Ho: There is no effect of different levels of OFSP flour and shredded coconut on the physical, microbiological, nutritional and sensory properties on buttermilk biscuits at ∝ = 0.05 and Ha: There is an effect of different levels of OFSP flour and shredded coconut on the physical, microbiological, nutritional and sensory properties on buttermilk biscuits at ∝ = 0.05. Methods OFSP flour was produced and combined with wheat flour at different ratios and infused with desiccated shredded coconut to produce six formulations of buttermilk biscuits: 100% wheat flour + 5% coconut (control 1), 100% wheat flour (control 2), 70% wheat flour + 30% OFSP flour + 5% coconut, 70% wheat flour + 30% OFSP flour, 50% wheat flour + 50% OFSP flour + 5% coconut and 50% wheat flour + 50% OFSP flour. The study followed a randomised 3 × 2 factorial design where each treatment was replicated four times giving 24 treatments. Physical, nutritional, sensory, microbiological and shelf-life analyses were determined for each buttermilk biscuit treatment. Results The study’s findings revealed that buttermilk biscuits formulated with 30% OFSP flour received the highest (p < 0.05) sensory evaluation scores for the majority of attributes and overall acceptability while the 100% wheat flour formulations received the lowest scores according to the 9-point hedonic scale. Notably, the inclusion of shredded coconut did not improve sensory attributes or overall acceptance of the buttermilk biscuits. The OFSP flour buttermilk biscuits contained protein, fat, fibre, moisture and ash. The 100% wheat flour treatments contained significantly higher levels of proteins and moisture than the OFSP flour buttermilk biscuits. The colour L* of the OFSP flour treatments were significantly lower than the 100% wheat flour treatments. There were no significant changes in spread-ratio, diameter and thickness of the buttermilk biscuits during storage. Furthermore, the microbiological quality was maintained as no growth of bacteria, yeasts and molds were observed. Discussion The OFSP flour with and without desiccated coconut produced acceptable buttermilk biscuits with less reliant on wheat flour. It is noteworthy that the protein content of the OFSP flour buttermilk biscuits was at an acceptable level even though it was lower than that in 100% wheat flour buttermilk biscuits. Food safety was maintained throughout storage which is crucial in the elimination of food borne diseases. The use of different baking parameters can be used for future studies to assess the effect of temperature on the quality of buttermilk biscuits.